1991
DOI: 10.1007/bf01871427
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of cardiac Na+ channels to antiarrhythmic drugs: The role of inactivation

Abstract: Elementary Na+ currents were recorded at 9 degrees C in inside-out patches from cultured neonatal rat heart myocytes. In characterizing the sensitivity of cooled, slowly inactivating cardiac Na+ channels to several antiarrhythmic drugs including propafenone, lidocaine and quinidine, the study aimed to define the role of Na+ inactivation for open channel blockade. In concentrations (1-10 mumol/liter) effective to depress NPo significantly, propafenone completely failed to influence the open state of slowly inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
8
1
1
Order By: Relevance
“…Even in the unmodified channel, the drug can associate and dissociate repeatedly with the open channel to produce "flickering." This result differs from that of Benz and Kohlhardt [4] who reported that the observation of repetitive blocking and unblocking events requires the removal of inactivation. In the simple sequential blocking model used in the analysis of the results, the total charge transferred during channel opening should, on average, be unchanged during the presence of drug [43,44].…”
Section: Discussioncontrasting
confidence: 84%
“…Even in the unmodified channel, the drug can associate and dissociate repeatedly with the open channel to produce "flickering." This result differs from that of Benz and Kohlhardt [4] who reported that the observation of repetitive blocking and unblocking events requires the removal of inactivation. In the simple sequential blocking model used in the analysis of the results, the total charge transferred during channel opening should, on average, be unchanged during the presence of drug [43,44].…”
Section: Discussioncontrasting
confidence: 84%
“…There is some controversy whether it blocks open channels. Our own studies, those of Zilberter et al (42) Benz and Kohlhardt (43), and Grant et al (27) show no change in mean open time, whereas others, e.g., Baumgarten et al (37), report a decrease in open time. There are fewer studies with disopyramide.…”
Section: Methodsmentioning
confidence: 45%
“…Additive and synergistic interactions between drugs that prolong APD and those that have high affinity for the inactive state of the Na þ channel have been predicted, e.g. lidocaine and quinidine [17,18]. Combination therapy using lower doses of each drug has indicated greater efficacy and fewer side effects than high doses of the individual drugs.…”
Section: Alternative Approaches To Targeting Conventional Ion Channelsmentioning
confidence: 98%